Kebijakan Pengembangan Jurnal Ilmiah - Redaksi Team (Fakultas Keperawatan Universitas Padjadjaran)
•[We must be] very careful of registring as well the person and time of •any new matter.., as the matter itselfe; whereby the honor of ye •invention will be inviolably preserved to all posterity [Oldenburg, 24 •November 1664] REGISTRATION • •all Ingenious men will be thereby incouraged to impart their knowledge •and discoveryes [Oldenburg, 3 December 1664] DISSEMINATION • •[I should not] neglect the opportunity of having some of my Memoirs •preserv’d, by being incorporated into a Collection, that is like to be as •lasting as usefull [Boyle, 1665] ARCHIVE • •[Philosophical Transactions should be] licensed under the charter by •the Council of the Society, being first reviewed by some of the members •of the same [Royal Society Order in Council 1 March 1665] •CERTIFICATION